2020
DOI: 10.1097/rlu.0000000000002833
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of 177Lu-PSMA-617 Radioligand Therapy in Metastatic Castration-Resistant Prostate Cancer Patients

Abstract: Purpose The aim of this study was to evaluate the efficacy and safety of 177Lu-PSMA-617 radioligand therapy in metastatic castration-resistant prostate cancer (mCRPC). Methods In this prospective, single-arm, single-institutional study, 90 mCRPC patients with progressive disease (PD) on second-line hormonal therapy and/or docetaxel chemotherapy were recruited for the study. All patients underwent diagnostic 68Ga-PSMA-HBED-CC PET/CT, prior to inclusion f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
85
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 33 publications
5
85
0
6
Order By: Relevance
“…Several studies have identified a link between the use of opioid pain medications and lower rates of PSA decline [11,12,23]. Similarly, in a prospective study of 90 patients, multivariate regression analysis showed that higher Eastern Cooperative Oncology Group (ECOG) score was associated with worse survival (HR: 10.69) [16].…”
Section: Reviewmentioning
confidence: 96%
See 3 more Smart Citations
“…Several studies have identified a link between the use of opioid pain medications and lower rates of PSA decline [11,12,23]. Similarly, in a prospective study of 90 patients, multivariate regression analysis showed that higher Eastern Cooperative Oncology Group (ECOG) score was associated with worse survival (HR: 10.69) [16].…”
Section: Reviewmentioning
confidence: 96%
“…Several studies have identified a link between the use of opioid pain medications and lower rates of PSA decline [ 11 , 12 , 23 ]. Similarly, in a prospective study of 90 patients, multivariate regression analysis showed that higher Eastern Cooperative Oncology Group (ECOG) score was associated with worse survival (HR: 10.69) [ 16 ]. Reflecting high tumor grade, elevated alkaline phosphatase, Gleason score of 10 or higher, and the presence of visceral metastases have been reported to be negative predictors of PSA response [ 7 , 12 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last decade, several treatment options for patients with metastatic, castrationresistant prostate cancer (mCRPC) were established, including abiraterone, enzalutamide, docetaxel and cabazitaxel [2]. More recently, radioligand therapy (RLT) with ( 177 Lu)Lu-labeled prostate-specific membrane antigen (PSMA) was developed and has shown promising results with regards to prostatespecific antigen (PSA) response rates and radiographic responses [3]. Retrospective as well as early prospective data confirmed the favourable safety profile of RLT [4,5].…”
Section: Introductionmentioning
confidence: 99%